2001
DOI: 10.1111/j.1348-0421.2001.tb01293.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Macrolide‐Resistant Mycoplasma pneumoniae Strains Isolated from Patients and Induced with Erythromycin In Vitro

Abstract: Some patients with Mycoplasma pneumoniae infection are clinically resistant to antibiotics such as erythromycin, c1arithromycin, or clindamycin. We isolated M. pneumoniae from such patients and found that one of three isolates showed a point mutation in the 238 rRNA gene. Furthermore, 141 EM-sensitive clinical isolates of M. pneumoniae were cultured in broth medium containing 100 fLglml of erythromycin (EM). Among 11 EM-resistant strains that grew in the medium, point mutations in the 238 rRNA were found in 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
159
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(164 citation statements)
references
References 12 publications
2
159
1
2
Order By: Relevance
“…Macrolides are generally considered the drugs of choice for treatment of children with M. pneumoniae infection (2). Since approximately the year 2000, macrolide-resistant (MR) M. pneumoniae has been appearing in Asia, Europe, Canada, and the USA (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The rate of macrolide resistance among M. pneumoniae infections ranges from 3 to 26z in Europe (9,15), from 63 to 97z in China (16)(17)(18)(19), and from 25 to 93z in Japan (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Macrolides are generally considered the drugs of choice for treatment of children with M. pneumoniae infection (2). Since approximately the year 2000, macrolide-resistant (MR) M. pneumoniae has been appearing in Asia, Europe, Canada, and the USA (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The rate of macrolide resistance among M. pneumoniae infections ranges from 3 to 26z in Europe (9,15), from 63 to 97z in China (16)(17)(18)(19), and from 25 to 93z in Japan (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…pneumonia isolates had mutations in domain V of the 23S rRNA gene (1,2,10,11). Several studies indicated that macrolide resistance in M. pneumoniae may have clinical significance in terms of diminished response to treatment with drugs in this class (2,12,13).…”
mentioning
confidence: 99%
“…A culture-independent MLVA method for use directly from clinical specimens has also been described (7). Macrolideresistant M. pneumoniae clinical isolates were first reported in the 1990s, and the incidence has been increasing ever since, with various rates in different geographic regions (16)(17)(18)(19)(20).In this study, we used MLVA, P1-RFLP analysis, and detection of macrolide resistance-associated mutations to compare characteristics of M. pneumoniae detected by PCR in clinical specimens from Beijing, China, and Sydney, Australia. Positive samples were identified using real-time PCR as described previously (21); only one sample from each patient was included.…”
mentioning
confidence: 99%
“…A culture-independent MLVA method for use directly from clinical specimens has also been described (7). Macrolideresistant M. pneumoniae clinical isolates were first reported in the 1990s, and the incidence has been increasing ever since, with various rates in different geographic regions (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%